2014
DOI: 10.1007/s11033-014-3671-y
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric proteins constructed from bacteriophage T7 gp4 and a putative primase–helicase from Arabidopsis thaliana

Abstract: An open reading frame from Arabidopsis thaliana, which is highly homologous to the human mitochondrial DNA helicase TWINKLE, was previously cloned, expressed, and shown to have DNA primase and DNA helicase activity. The level of DNA primase activity of this Arabidopsis Twinkle homolog (ATH) was low, perhaps due to an incomplete zinc binding domain (ZBD). In this study, N-terminal truncations of ATH implicate residues 80-102 interact with the RNA polymerase domain (RPD). In addition, chimeric proteins, construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Both recombinant proteins were purified to homogeneity after three chromatographic steps, with similar purity as a recombinant primase module (residues 1–262) from the T7 primase-helicase gene used as a control during this study (Figure 2A ). Previous biochemical characterizations of AtTwinkle indicated that this protein is active on single-stranded M13 templates ( 28 , 29 , 32 ). To assess if our purified proteins exhibit oligoribonucleotide synthesis activity we used a random heptaoligonucleotide as a template and assayed AtPrimase and T7 primase fragments for ribonucleotide synthesis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Both recombinant proteins were purified to homogeneity after three chromatographic steps, with similar purity as a recombinant primase module (residues 1–262) from the T7 primase-helicase gene used as a control during this study (Figure 2A ). Previous biochemical characterizations of AtTwinkle indicated that this protein is active on single-stranded M13 templates ( 28 , 29 , 32 ). To assess if our purified proteins exhibit oligoribonucleotide synthesis activity we used a random heptaoligonucleotide as a template and assayed AtPrimase and T7 primase fragments for ribonucleotide synthesis.…”
Section: Resultsmentioning
confidence: 97%
“…Motif I corresponds to the ZBD necessary for template recognition ( 26 ), whereas regions II to VI are located in the RNAP domain. In vitro characterization of AtTwinkle demonstrated that this enzyme has both primase and helicase activities ( 28 , 29 , 32 ). However, its preferred ssDNA template sequence, its putative role in organellar replication, and its interactions with plant organellar DNA polymerases remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the ZFD fulfills roles in template recognition, primer stability, and primer transfer [ 5 , 18 , 20 , 21 ]. The Twinkle ortholog of the plant model Arabidopsis thaliana (AtTwinkle) is active, both as a primase and as a helicase [ 13 , 22 , 23 ]. Contrary to all primases characterized to date, the primase module of AtTwinkle recognizes two nucleotides (instead of one) as cryptic elements.…”
Section: Introductionmentioning
confidence: 99%